A proposal for a test of Weak Equivalence Principle with improved accuracy using a cryogenic differential accelerometer installed on a pendulum. Issue 2 (15th January 2016) - Iafolla, V.A.; Fiorenza, E.; Lefevre, C.; Lucchesi, D.M.; Lucente, M.; Magnafico, C.; Nozzoli, S.; Peron, R.; Santoli, F.; Lorenzini, E.C.; Milyukov, V.; Shapiro, I.I.; et al.
Abstract: We present here the concept for a new experimental test of the Weak Equivalence Principle (WEP) carried out in the gravity field of the Sun. The WEP, stating the independence of the gravitational acceleration a body is subject to from its mass and composition, is at the basis of general relativity theory and more in general of metric theories of gravitation. It is therefore very important to test it to the precision allowable by current technology. The experiment here proposed aims at measuring the relative acceleration of two test masses in free fall, searching for a possible violation of the WEP, which would show up as a non-zero acceleration signal. The core of the experiment is constituted by a differential accelerometer with zero baseline, whose central elements are two test masses of different materials. This differential accelerometer is placed on a pendulum, in such a way as to make the common center of mass coincident with the center of mass of the pendulum itself. Ensuring a very precise centering, such a system should provide a high degree of attenuation of the local seismic noise, which — together with an integration time of the order of tens of days — would allow a test of the WEP with an accuracy improved by at least an order of magnitude with respect to the best measurements achieved so far. One of the strengths of this proposal is the know-how acquired from a previous study and technology development (GReAT: General Relativity Accuracy Test) that involved a test of the WEP in the gravity field of the Earth, in free fall inside a co-moving capsule released from a stratospheric balloon. The concept of the experiment is introduced, with particular attention to the differential accelerometer and its accommodation on the pendulum. A preliminary estimate of the attainable precision is given, along with a critical analysis of the associated challenges.